2015
DOI: 10.1158/1940-6207.capr-14-0357
|View full text |Cite
|
Sign up to set email alerts
|

3,6-Dihydroxyflavone Suppresses Breast Carcinogenesis by Epigenetically Regulating miR-34a and miR-21

Abstract: Our previous study selected a promising chemopreventive agent 3,6-dihydroxyflavone (3,6-DHF) and found that 3,6-DHF significantly upregulates miR-34a and downregulates miR-21 in breast carcinogenesis, yet the upstream and downstream events of the anticancer mechanism remain unclear. The present study showed that 3,6-DHF cotreatment effectively inhibits carcinogens-induced breast carcinogenic transformation in human breast epithelial MCF10A cells. The data revealed the significant downregulation of miR-34a and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
(28 reference statements)
2
25
0
Order By: Relevance
“…Aberrant regulation of miRNAs is involved in controlling stemness in multiple cancers by modulating stemness-related genes [39][40][41]. MiR-34a is a tumor suppressor miRNA and is downregulated in many malignancies, for example, human liver cancer [10,11]. Interestingly, miR-34a might be regulated by DNMT1 through promoter methylation in cancer cells or CSLCs [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant regulation of miRNAs is involved in controlling stemness in multiple cancers by modulating stemness-related genes [39][40][41]. MiR-34a is a tumor suppressor miRNA and is downregulated in many malignancies, for example, human liver cancer [10,11]. Interestingly, miR-34a might be regulated by DNMT1 through promoter methylation in cancer cells or CSLCs [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DNMT1 is important in maintaining cancer stem cells (CSCs) in a self-renewal capability and promoting tumorigenesis, for example, mammary CSCs [8] and leukemia stem cells [9]. Importantly, Peng et al reported that DNMT1 repression could upregulate miR-34a to induce cytotoxicity and apoptosis in breast cancer cells [10]. Chamani et al showed that DNMT1 inhibition increases miR-34a expression, resulting in reduced viability of both Hep G2 and Huh7 cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic silencing of miR-34a by aberrant CpG methylation frequently occurs in various types of human cancer (39). Dihydroxyflavone has been reported to demethylate miR-34a and increases its expression in breast cancer cells (40). Therefore, we hypothesize that ginkgetin controls the expression of miR-34a through its epigenetic modulation; however, ginkgetin did not affect the demethylation of miR-34a (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, miR‐21 was suppressed during both early (1 week) and later (2 weeks) osteogenic differentiation (Figure B). To further analyze the possible mechanism of how adrenaline inhibits miR‐21, we focused on the histone modification of the miR‐21 promoter (Peng et al, ). As noted in Figure C, acetyl‐H3K9 antibody ChIP analysis revealed that osteogenic induction medium significantly induced the enrichment of acetylated H3K9 on the miR21 promoter, whereas adrenaline inhibited the enrichment.…”
Section: Resultsmentioning
confidence: 99%